Bone Marrow Adipocytes, Adipocytokines, and Breast Cancer Cells: Novel Implications in Bone Metastasis of Breast Cancer - Liu, Chang; Zhao, Qian; Yu, Xijie (Frontiers in Oncology, 2020)
Accumulating discoveries highlight the importance of interaction between marrow stromal cells and cancer cells for bone metastasis. Bone is the most common metastatic site of breast cancer and bone marrow adipocytes (BMAs) constitute the most abundant component of the bone marrow microenvironment. BMAs are unique in their origin and location, and recently they are found to serve as an endocrine organ that secretes adipokines, cytokines, chemokines, and growth factors. It is reasonable to speculate that BMAs contribute to the modification of bone metastatic microenvironment and affecting metastatic breast cancer cells in the bone marrow. Indeed, BMAs may participate in bone metastasis of breast cancer through regulation of recruitment, invasion, survival, colonization, proliferation, angiogenesis, and immune modulation by their production of various adipocytokines. In this review, we provide an overview of research progress, focusing on adipocytokines secreted by BMAs and their potential roles for bone metastasis of breast cancer, and investigating the mechanisms mediating the interaction between BMAs and metastatic breast cancer cells. Based on current findings, BMAs may function as a pivotal modulator of bone metastasis of breast cancer, therefore targeting BMAs combined with conventional treatment programs might present a promising therapeutic option.